Lean leadership in major projects: from "predict and provide" to "predict and prevent". Issue 6 (15th May 2018) - Holweg, Matthias; Maylor, Harvey
Abstract : Purpose: The purpose of this paper is to understand the context of major projects and their management from an OM perspective; the authors provide a foundation for exploring how the body of work on lean production (the "old" theory) can contribute to the development of major projects (the "new" context). In doing so, it extends the prevailing economic approach to major projects (best described as "predict and provide") and posits the development of an alternative approach based on extending the lean production logic to this new context (referred to as "predict and prevent"). Design/methodology/approach: The paper investigates the scope for adopting lean practices in context of major project. To this effect the authors review the current state of both lean thinking and major project management, and use "Universal Credit" as an exploratory case study to illustrate and verify the arguments in practice. Findings: Two main findings are proposed: first, the authors demonstrate the inherent performance challenge of major projects in OM terms, which the authors argue presents significant scope for the application of OM concepts to improve major project performance. Second, using lean thinking as framing, the authors identify three distinct process levels and common wastes in major projects, and identify five principles how lean could improve the delivery of major projects. Research limitations/implications: Major projects present an untapped area for OM research; based on the exploratory case the authors propose ways how OM concepts can be applied to this new context. Further research will be needed to validate and generalise. Practical implications: Major projects, including organisational transformations, IT-enabled change, major events and large infrastructure projects, constitute a large proportion of economic activity. Despite their prominence, however, they are also commonly associated with low success rates. This paper provides one route for exploring how a successful set of principles could be applied to improving their performance. Originality/value: This work translates a popular set of ideas from OM to strengthening a relatively neglected context within OM. An agenda for further research is suggested to support the development of this application.